10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
With the expansion of internet-based health care, value co-creation behaviors of patients with chronic diseases have become increasingly important. However, appropriate instruments for assessing such behaviors among community-dwelling patients in digital health contexts remain limited. This study aimed to psychometrically evaluate the effort in value cocreation activities (EVCA) questionnaire using the Rasch model to establish a valid and reliable measure of patient engagement in value cocreation in digital health. A Chinese version of the EVCA questionnaire, developed following standard procedures for translation and cultural adaptation, was administered to a sample of 417 community-dwelling patients with chronic diseases. Rasch analysis was applied to examine unidimensionality, local dependency, category functioning, item fit, reliability and separation, differential item functioning (DIF) by gender and age, the item-person map, and the score conversion table. The final EVCA showed unidimensionality and no local dependency, with all items demonstrating acceptable fit, satisfactory person and item separation, no significant DIF by gender or age, and greater efficiency of the 4-point than the original 7-point structure. Patients considered the easiest item to complete as item 8, "Healthy diet," while the most difficult items were item 10, "Seeking information," and item 3, "Proactive involvement in decision making." The EVCA exhibits a good fit to the Rasch model and robust psychometric properties, supporting its reliability and validity for assessing patient engagement in value co-creation in digital health settings.